Lithium ion battery and method of manufacturing the same
Patent Information
- Application Number
- CN202611279779.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]本发明的主要目的在于提供一种锂离子电池及其制备方法,以解决现有技术中锰系锂离子电池存在循环性能较差的问题
[0018]应用本发明的技术方案,本申请的锂离子电池通过在正极活性层和负极活性层中同时引入氮掺杂多孔碳纳材料能够协同解决磷酸锰铁锂材料的电导率较低以及Mn2+溶出导致的循环性能劣化的问题。具体原理如下:1)氮掺杂多孔碳纳米材料通过SP2/SP3杂化碳骨架与氮原子的协同作用,能够降低材料的费米能级至导带附近,同时利用氮原子的孤对电子增加电流密度,将导电剂的电导率增加3倍左右,从而提高极片的电导率,进而有效缓解LMFP材料电导率较低带来的电芯充放电过程中的极化严重和副反应增多导致电池长期循环后性能衰减的问题。2)氮掺杂多孔碳纳材料中掺杂的氮元素含有的孤对电子能够与Mn2+产生络合作用,从而将LMFP正极材料溶出的Mn2+固定在其表面,阻止Mn2+迁移到负极的表面。同时在负极活性层中的第二氮掺杂多孔碳纳米材料也能够与从正极溶出并迁移到负极区域的Mn2+产生络合作用,实现Mn2+在负极界面的“原位捕获”与“原位固定”。因此,通过正极和负极的协同络合作用,能够有效阻断Mn2+对负极SEI膜的破坏,避免SEI膜反复修复导致的活性锂与电解液持续消耗,从而提高电池的循环性能。3)氮掺杂多孔碳纳材料具有的高比表面积使其与电解液的亲和性较高,能够提升极片的保液能力,从而不仅能够更好地维持电池内部的离子传输通道畅通,减少电解液的消耗和副反应的发生,还能够有效减少电解液与电极材料的直接接触,降低副反应的发生,如锰离子对电解液的催化分解,从而延长电池的循环寿命。同时,充足的电解液能够保证锂离子在正负极之间的高效扩散,从而降低极化现象,进而提高电池的充放电效率和循环稳定性。综上,本申请采用上述正极和负极的锂离子电池具有良好的长循环性能、较高的能量密度和安全性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a lithium-ion battery and its preparation method. Background Technology
[0002] Lithium manganese iron phosphate (LMFP) lithium-ion batteries (LIBs), as a lithium battery system between lithium iron phosphate and ternary lithium-ion batteries, have both high safety and high energy, but the cycle performance of LMFP lithium-ion batteries is one of the reasons that limits their competitiveness.
[0003] Currently, the main reasons for the poor cycle performance of LMFP batteries are as follows: 1) The conductivity of lithium manganese iron phosphate material itself is relatively low (approximately 10). -13 S / cm), which restricts electron transport and lithium-ion diffusion. The discontinuous FeO6 / MnO6 octahedral network and PO4 tetrahedron in its crystal structure hinder electron transfer and lithium-ion insertion / extraction, resulting in severe polarization during charge and discharge, increased side reactions, and performance degradation after long-term cycling; 2) Jahn-Teller effect: Mn 3+ The asymmetric electron distribution causes distortion of the MnO6 octahedron, and the acid produced by the decomposition of the electrolyte corrodes the manganese ions at the positive electrode, accelerating the decomposition of MnO6. 3+ The disproportionation reaction produces Mn 2+ and Mn 4+ Dissolving in the electrolyte leads to the loss of positive electrode active material and damages the negative electrode SEI film. The repair of the SEI film consumes active lithium ions and electrolyte, resulting in a gradual decrease in the cell's cycle performance.
[0004] Currently, the main methods to address the low conductivity of LMFP materials are as follows: 1) Introducing carbon nanotubes (CNTs) to form a long-range conductive network inside the cell, utilizing their high conductivity and aspect ratio, to improve the polarization problem caused by the low conductivity of LMFP itself. However, the high price of CNTs increases the cost of the cell. 2) Nano-sized LMFP cathode materials to improve the polarization problem caused by the low conductivity of LMFP itself. However, nano-sized LMFP materials increase their specific surface area, thereby increasing the contact area with the electrolyte. This leads to more side reactions at the LMFP-electrolyte interface, resulting in poor cycle performance of the cell. At the same time, nano-sized LMFP also reduces electrode compaction, thereby reducing the energy density of the cell.
[0005] To address the issues of negative electrode SEI film damage and repair processes caused by manganese leaching from lithium manganese iron phosphate, which consume active lithium and electrolyte, the following methods are mainly employed: 1) Adding nitrogen-containing additives and Mn to the electrolyte. 2+ Complexation, thereby reducing Mn 2+The damage to the SEI film on the negative electrode improves the cycle performance of the battery cell, but the nitrogen-containing additives in the electrolyte complex with Mn 2+ It can only reduce Mn 2+ The improvement effect on the migration rate is limited. Furthermore, nitrogen-containing additives preferentially form an SEI film at the negative electrode, increasing cell impedance. Additionally, nitrogen-containing additives consume active lithium during negative electrode reduction, leading to deterioration of the cell's cycle performance; 2) Mn 2+ The membrane trapping technology, by reducing the membrane pore size (<20nm), traps solvated Mn. 2+ Thus preventing Mn 2+ The cells migrate to the negative electrode surface, but reducing the pore size of the separator increases the cell impedance, thereby increasing cell polarization and causing a decrease in the cell's rate performance and cycle performance.
[0006] Therefore, there is a need to develop manganese-based lithium-ion batteries with long cycle performance. Summary of the Invention
[0007] The main objective of this invention is to provide a lithium-ion battery and its preparation method to solve the problem of poor cycle performance in existing manganese-based lithium-ion batteries.
[0008] To achieve the above objectives, according to one aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode, a negative electrode, and a separator. The positive electrode includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector. The negative electrode includes a negative current collector and a negative active layer disposed on at least one side surface of the negative current collector. The positive active layer includes a positive electrode material, a first nitrogen-doped porous carbon nanomaterial, a first conductive agent, and a first binder. The positive electrode material includes lithium manganese iron phosphate. The mass percentage of the first nitrogen-doped porous carbon nanomaterial in the positive active layer is 0.05~1.0%. The negative active layer includes a negative electrode material, a second nitrogen-doped porous carbon nanomaterial, a second conductive agent, and a second binder. The mass percentage of the second nitrogen-doped porous carbon nanomaterial in the negative active layer is 0.05~1.0%.
[0009] Furthermore, the mass ratio of the positive electrode material, the first nitrogen-doped porous carbon nanomaterial, the first conductive agent and the first binder in the positive electrode active layer is (94~98):(0.05~1):(0.2~2.5):(1~3.5).
[0010] Furthermore, the first nitrogen-doped porous carbon nanomaterial is selected from any one or more of nitrogen-doped porous carbon nanospheres, nitrogen-doped carbon nanofibers, and nitrogen-doped carbon nanosheets; the mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial is 1-25%; and the specific surface area of the first nitrogen-doped porous carbon nanomaterial is 500-1500 m². 2 / g; D50 particle size of nitrogen-doped porous carbon nanospheres <1μm; the first nitrogen-doped porous carbon nanomaterial includes a third nitrogen-doped porous carbon nanomaterial and a fourth nitrogen-doped porous carbon nanomaterial; wherein, the mass ratio of the third nitrogen-doped porous carbon nanomaterial to the fourth nitrogen-doped porous carbon nanomaterial is 1:(0.1~0.8); the mass content of nitrogen in the third nitrogen-doped porous carbon nanomaterial is 5~15% lower than that in the fourth nitrogen-doped porous carbon nanomaterial; the specific surface area of the third nitrogen-doped porous carbon nanomaterial is 200~400m² smaller than that of the fourth nitrogen-doped porous carbon nanomaterial. 2 / g.
[0011] Furthermore, the aforementioned cathode material also includes any one or more of lithium iron phosphate, lithium-rich manganese-based cathode materials, and ternary cathode materials; and / or, the first conductive agent is conductive carbon black and / or carbon nanotubes; when the first conductive agent is a combination of conductive carbon black and carbon nanotubes, the mass ratio of conductive carbon black to carbon nanotubes is 0.3~1.5:0.05~1.0; and / or, the first binder is polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer.
[0012] Furthermore, the mass ratio of the negative electrode material, the second nitrogen-doped porous carbon nanomaterial, the second conductive agent, and the second binder in the negative electrode active layer is (94~98):(0.05~1):(0.2~2.5):(1~3.5).
[0013] Furthermore, the second nitrogen-doped porous carbon nanomaterial is selected from any one or more of nitrogen-doped porous carbon nanospheres, nitrogen-doped carbon nanofibers, and nitrogen-doped carbon nanosheets; the mass content of nitrogen in the second nitrogen-doped porous carbon nanomaterial is 1-25%; and the specific surface area of the second nitrogen-doped porous carbon nanomaterial is 500-1500 m². 2 / g; D50 particle size of nitrogen-doped porous carbon nanospheres <1μm; the second nitrogen-doped porous carbon nanomaterial includes a fifth nitrogen-doped porous carbon nanomaterial and a sixth nitrogen-doped porous carbon nanomaterial; wherein, the mass ratio of the fifth nitrogen-doped porous carbon nanomaterial to the sixth nitrogen-doped porous carbon nanomaterial is 1:(0.1~0.5); the mass content of nitrogen in the fifth nitrogen-doped porous carbon nanomaterial is 5~15% lower than that in the sixth nitrogen-doped porous carbon nanomaterial; the specific surface area of the fifth nitrogen-doped porous carbon nanomaterial is 200~400m² smaller than that of the sixth nitrogen-doped porous carbon nanomaterial. 2 / g.
[0014] Furthermore, the negative electrode material is selected from any one or more of natural graphite, artificial graphite, and silicon carbide materials; and / or, the second conductive agent is conductive carbon black; and / or, the second binder is selected from any one or more of sodium carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber latex.
[0015] According to another aspect of the present invention, a method for preparing the above-mentioned lithium-ion battery is provided, the method comprising: step S1, mixing raw materials including a positive electrode material, a first nitrogen-doped porous carbon nanomaterial, a first conductive agent, a first binder and a first solvent to obtain a positive electrode slurry; coating the positive electrode slurry onto at least one side surface of a positive electrode current collector to form a positive electrode active layer to obtain a positive electrode sheet; step S2, mixing raw materials including a negative electrode material, a second nitrogen-doped porous carbon nanomaterial, a second conductive agent, a second binder and a second solvent to obtain a negative electrode slurry; coating the negative electrode slurry onto at least one side surface of a negative electrode current collector to form a negative electrode active layer to obtain a negative electrode sheet; and step S3, assembling the positive electrode sheet, a separator and a negative electrode sheet to obtain a lithium-ion battery.
[0016] Further, in step S1 above, the first solvent is N-methylpyrrolidone; and / or, the solid content of the positive electrode slurry is 55-68%; and / or, the areal density of the single-sided positive electrode active layer is 87-91 g / m². 2 .
[0017] Further, in step S2 above, the second solvent is water; and / or, the solid content of the negative electrode slurry is 48-58%; and / or, the areal density of the single-sided negative electrode active layer is 87-91 g / m². 2 .
[0018] By applying the technical solution of this invention, the lithium-ion battery of this application can synergistically solve the problems of low conductivity and Mn content in lithium manganese iron phosphate materials by simultaneously introducing nitrogen-doped porous carbon nanomaterials into both the positive and negative electrode active layers. 2+ The problem of deteriorated cycling performance due to dissolution. The specific principle is as follows: 1) Nitrogen-doped porous carbon nanomaterials are processed through SP... 2 / SP 3 The synergistic effect of the hybrid carbon framework and nitrogen atoms can lower the Fermi level of the material to near the conduction band. Simultaneously, the lone pair electrons of nitrogen atoms increase the current density, increasing the conductivity of the conductive agent by approximately three times, thereby improving the conductivity of the electrode. This effectively alleviates the problem of severe polarization and increased side reactions during the charging and discharging process of the battery cell, which is caused by the low conductivity of LMFP materials, leading to performance degradation after long-term cycling. 2) In nitrogen-doped porous carbon nanomaterials, the lone pair electrons of the nitrogen doped element can interact with Mn... 2+ Complexation occurs, thereby dissolving the Mn from the LMFP cathode material. 2+ Fixed on its surface, preventing Mn 2+ The nitrogen-doped porous carbon nanomaterials in the negative electrode active layer can also migrate to the surface of the negative electrode. Simultaneously, the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer can also interact with the Mn dissolved from the positive electrode and migrated to the negative electrode region. 2+ To generate a complexation effect and realize Mn 2+"In-situ capture" and "in-situ fixation" occur at the negative electrode interface. Therefore, through the synergistic complexation of the positive and negative electrodes, Mn can be effectively blocked. 2+ The damage to the SEI film on the negative electrode is prevented, avoiding repeated repairs that lead to continuous consumption of active lithium and electrolyte, thus improving the battery's cycle performance. 3) The high specific surface area of nitrogen-doped porous carbon nanomaterials gives them a high affinity for the electrolyte, enhancing the electrolyte retention capacity of the electrode. This not only better maintains the unobstructed ion transport channels inside the battery, reducing electrolyte consumption and side reactions, but also effectively reduces direct contact between the electrolyte and electrode materials, minimizing side reactions such as the catalytic decomposition of the electrolyte by manganese ions, thereby extending the battery's cycle life. Simultaneously, sufficient electrolyte ensures efficient diffusion of lithium ions between the positive and negative electrodes, reducing polarization and improving the battery's charge / discharge efficiency and cycle stability. In summary, the lithium-ion battery using the above-mentioned positive and negative electrodes exhibits excellent long-cycle performance, high energy density, and safety. Detailed Implementation
[0019] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.
[0020] As analyzed in the background section of this application, existing manganese-based lithium-ion batteries suffer from poor cycle performance. To address these issues, this application provides a lithium-ion battery and its preparation method.
[0021] In a typical embodiment of this application, a lithium-ion battery is provided, including a positive electrode, a negative electrode, and a separator. The positive electrode includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector. The negative electrode includes a negative current collector and a negative active layer disposed on at least one side surface of the negative current collector. The positive active layer includes a positive electrode material, a first nitrogen-doped porous carbon nanomaterial, a first conductive agent, and a first binder. The positive electrode material includes lithium manganese iron phosphate. The mass percentage of the first nitrogen-doped porous carbon nanomaterial in the positive active layer is 0.05~1.0%. The negative active layer includes a negative electrode material, a second nitrogen-doped porous carbon nanomaterial, a second conductive agent, and a second binder. The mass percentage of the second nitrogen-doped porous carbon nanomaterial in the negative active layer is 0.05~1.0%.
[0022] The lithium-ion battery of this application can synergistically solve the problems of low conductivity and Mn content in lithium manganese iron phosphate materials by simultaneously introducing nitrogen-doped porous carbon nanomaterials into both the positive and negative electrode active layers. 2+ The problem of deteriorated cycling performance due to dissolution. The specific principle is as follows: 1) Nitrogen-doped porous carbon nanomaterials are processed through SP... 2 / SP 3The synergistic effect of the hybrid carbon framework and nitrogen atoms can lower the Fermi level of the material to near the conduction band. Simultaneously, the lone pair electrons of nitrogen atoms increase the current density, increasing the conductivity of the conductive agent by approximately three times, thereby improving the conductivity of the electrode. This effectively alleviates the problem of severe polarization and increased side reactions during the charging and discharging process of the battery cell, which is caused by the low conductivity of LMFP materials, leading to performance degradation after long-term cycling. 2) In nitrogen-doped porous carbon nanomaterials, the lone pair electrons of the nitrogen doped element can interact with Mn... 2+ Complexation occurs, thereby dissolving the Mn from the LMFP cathode material. 2+ Fixed on its surface, preventing Mn 2+ The nitrogen-doped porous carbon nanomaterials in the negative electrode active layer can also migrate to the surface of the negative electrode. Simultaneously, the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer can also interact with the Mn dissolved from the positive electrode and migrated to the negative electrode region. 2+ To generate a complexation effect and realize Mn 2+ "In-situ capture" and "in-situ fixation" occur at the negative electrode interface. Therefore, through the synergistic complexation of the positive and negative electrodes, Mn can be effectively blocked. 2+ The damage to the SEI film on the negative electrode is prevented, avoiding repeated repairs that lead to continuous consumption of active lithium and electrolyte, thus improving the battery's cycle performance. 3) The high specific surface area of nitrogen-doped porous carbon nanomaterials gives them a high affinity for the electrolyte, enhancing the electrolyte retention capacity of the electrode. This not only better maintains the unobstructed ion transport channels inside the battery, reducing electrolyte consumption and side reactions, but also effectively reduces direct contact between the electrolyte and electrode materials, minimizing side reactions such as the catalytic decomposition of the electrolyte by manganese ions, thereby extending the battery's cycle life. Simultaneously, sufficient electrolyte ensures efficient diffusion of lithium ions between the positive and negative electrodes, reducing polarization and improving the battery's charge / discharge efficiency and cycle stability. In summary, the lithium-ion battery using the above-mentioned positive and negative electrodes exhibits excellent long-cycle performance, high energy density, and safety.
[0023] Nitrogen-doped porous carbon nanomaterials can be prepared in-house or purchased. Furthermore, the mass percentage of the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%, etc. The mass percentage of the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%, etc.
[0024] In one embodiment of this application, the mass ratio of the positive electrode material, the first nitrogen-doped porous carbon nanomaterial, the first conductive agent and the first binder in the positive electrode active layer is (94~98):(0.05~1):(0.2~2.5):(1~3.5).
[0025] Preferably controlling the mass ratio of the positive electrode material, the first nitrogen-doped porous carbon nanomaterial, the first conductive agent, and the first binder in the positive electrode active layer within the aforementioned range helps to further improve the conductivity, energy density, and cycle performance of the positive electrode sheet. Controlling the mass percentage of the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer to 0.05~1% not only helps to further improve the conductivity of the positive electrode sheet but also reduces Mn content. 2+ Dissolution improves the battery's long-cycle performance and also helps improve the positive electrode's liquid retention capacity, thereby reducing electrolyte consumption and side reactions, and ultimately improving the battery's cycle life.
[0026] In one embodiment of this application, the first nitrogen-doped porous carbon nanomaterial is selected from any one or more of nitrogen-doped porous carbon nanospheres, nitrogen-doped carbon nanofibers, and nitrogen-doped carbon nanosheets; the mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial is 1-25%; and the specific surface area of the first nitrogen-doped porous carbon nanomaterial is 500-1500 m². 2 / g; D50 particle size of nitrogen-doped porous carbon nanospheres <1μm; the first nitrogen-doped porous carbon nanomaterial includes a third nitrogen-doped porous carbon nanomaterial and a fourth nitrogen-doped porous carbon nanomaterial; wherein, the mass ratio of the third nitrogen-doped porous carbon nanomaterial to the fourth nitrogen-doped porous carbon nanomaterial is 1:(0.1~0.8); the mass content of nitrogen in the third nitrogen-doped porous carbon nanomaterial is 5~10% lower than that in the fourth nitrogen-doped porous carbon nanomaterial; the specific surface area of the third nitrogen-doped porous carbon nanomaterial is 200~400m² smaller than that of the fourth nitrogen-doped porous carbon nanomaterial. 2 / g.
[0027] Preferably controlling the type of the first nitrogen-doped porous carbon nanomaterial spheres within the aforementioned range helps to improve the conductivity of the cathode, reduce polarization, and minimize side reactions. Simultaneously, it also facilitates the interaction of the lone pair electrons of nitrogen atoms with Mn. 2+ The complexation effect of Mn dissolved from the LMFP cathode material 2+ By fixing it to its surface, it prevents the nitrogen from migrating to the negative electrode surface and damaging the SEI film, thus simultaneously achieving the dual functions of enhanced conductivity and improved cycle stability. In the first nitrogen-doped porous carbon nanomaterial, if the nitrogen content is too low, there will be insufficient lone pair electrons, making it difficult to improve conductivity and complex Mn. 2+ Excessive nitrogen content can disrupt the graphitization of the carbon structure, reducing electron transport efficiency and thus affecting the rate performance of the battery. Therefore, this application controls the nitrogen content in the first nitrogen-doped porous carbon nanomaterial within the aforementioned range, which helps to improve the conductivity of the cathode while simultaneously enhancing its ability to absorb Mn. 2+The trapping ability of Mn is enhanced. Preferably, controlling the specific surface area of the first nitrogen-doped porous carbon nanomaterial within the above-mentioned range helps to provide abundant active sites and enhance the trapping ability of Mn. 2+ This enhances the trapping ability of the cathode and improves its liquid retention capacity, keeping the ion transport channels inside the battery unobstructed, thereby reducing electrolyte consumption and side reactions. Controlling the D50 particle size of nitrogen-doped carbon nanospheres within the aforementioned range helps them to be uniformly distributed in the cathode active layer and in close contact with LMFP particles, constructing a highly efficient three-dimensional conductive network and achieving Mn... 2+ It captures lithium ions in situ without blocking the lithium-ion transport channels, thereby simultaneously improving the conductivity and cycle stability of the positive electrode.
[0028] Furthermore, the mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial can be 1%, 3%, 5%, 7%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 25%, etc. The specific surface area of the first nitrogen-doped porous carbon nanomaterial can be 500 m². 2 / g、700m 2 / g、900m 2 / g、1100m 2 / g、1200m 2 / g, 1500m 2 / g etc. The D50 particle size of nitrogen-doped porous carbon nanospheres can be 0.1μm, 0.3μm, 0.5μm, 0.7μm, 0.9μm, etc.
[0029] The preferred first nitrogen-doped porous carbon nanomaterial includes a third nitrogen-doped porous carbon nanomaterial and a fourth nitrogen-doped porous carbon nanomaterial with a mass ratio within the above-mentioned range. By setting a gradient in nitrogen content and specific surface area between the two, their synergistic effect is enhanced, thereby further improving their conductivity and their affinity for Mn. 2+ Its complexing ability.
[0030] Preferably, the nitrogen content in the third nitrogen-doped porous carbon nanomaterial is 3-8% by mass, and the nitrogen content in the fourth nitrogen-doped porous carbon nanomaterial is 12-20% by mass. Preferably, the nitrogen content in the third nitrogen-doped porous carbon nanomaterial is lower than that in the fourth nitrogen-doped porous carbon nanomaterial by the aforementioned range. Simultaneously, the specific surface area of the third nitrogen-doped porous carbon nanomaterial is preferably 500-800 m². 2 / g, the specific surface area of the fourth nitrogen-doped porous carbon nanomaterial is 1000~1200m². 2 / g, preferably, the specific surface area of the third nitrogen-doped porous carbon nanomaterial is smaller than that of the fourth nitrogen-doped porous carbon nanomaterial within the range mentioned above. The third nitrogen-doped porous carbon nanomaterial has a relatively low nitrogen content and a relatively small specific surface area, and it mainly plays a role in constructing the basic conductive network, thereby improving the overall electron transport efficiency of the positive electrode. The fourth nitrogen-doped porous carbon nanomaterial has a relatively high nitrogen content and a relatively large specific surface area, and it mainly efficiently captures dissolved Mn. 2 + To prevent Mn 2+ The material migrates to the surface of the negative electrode and damages the SEI film. The two work together to achieve a "conductivity + retention" functional partition: the low-nitrogen, small-specific-surface-area third nitrogen-doped porous carbon nanomaterial provides a stable framework, while the high-nitrogen, large-specific-surface-area third nitrogen-doped porous carbon nanomaterial focuses on interface protection.
[0031] A seventh nitrogen-doped porous carbon nanomaterial can be added as needed, with its nitrogen content and specific surface area falling between those of the third and fourth nitrogen-doped porous carbon nanomaterials, further optimizing the gradient effect of nitrogen content and specific surface area.
[0032] In one embodiment of this application, the cathode material further includes any one or more of lithium iron phosphate, lithium-rich manganese-based cathode material, and ternary cathode material; and / or, the first conductive agent is conductive carbon black and / or carbon nanotubes; when the first conductive agent is a combination of conductive carbon black and carbon nanotubes, the mass ratio of conductive carbon black to carbon nanotubes is (0.3~1.5):(0.05~1.0); and / or, the first binder is polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer.
[0033] Lithium manganese iron phosphate materials can also be used in combination with other types of cathode materials mentioned above, helping to meet the performance requirements of different batteries. Preferably, the type of the first conductive agent is within the above-mentioned range, which helps to improve the conductivity of the cathode sheet. When the first conductive agent is preferably a combination of conductive carbon black and carbon nanotubes (CNTs), the conductive carbon black enhances local conductivity, and the CNTs construct long-range conductive pathways. Controlling the mass ratio of conductive carbon black to carbon nanotubes within the above-mentioned range helps to further improve the conductivity of the cathode sheet. Adding nitrogen-doped porous carbon nanomaterials can also replace high-cost CNTs, reducing the amount of CNTs added while achieving the same conductive network construction, thereby reducing the material cost. Preferably, the type of the first binder is within the above-mentioned range, which helps to improve the adhesion of the cathode active layer, thereby improving the structural integrity of the electrode during long-term cycling and reducing the shedding of active material.
[0034] In one embodiment of this application, the mass ratio of the negative electrode material, the second nitrogen-doped porous carbon nanomaterial, the second conductive agent, and the second binder in the negative electrode active layer is (94~98):(0.05~1):(0.2~2.5):(1~3.5).
[0035] Preferably controlling the mass ratio of the negative electrode material, the second nitrogen-doped porous carbon nanomaterial, the second conductive agent, and the second binder within the aforementioned range helps to further improve the conductivity, energy density, and cycle performance of the negative electrode sheet. Preferably, the mass percentage of the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer is 0.05~1%, which not only helps to capture and fix Mn dissolved from the positive electrode and migrated to the negative electrode surface, but also... 2+ This reduces damage to the solid electrolyte interphase (SEI) membrane and also helps improve the liquid retention capacity of the negative electrode, thereby helping to keep the ion transport channels inside the battery unobstructed, reducing electrolyte consumption and the occurrence of side reactions.
[0036] In one embodiment of this application, the second nitrogen-doped porous carbon nanomaterial is selected from any one or more of nitrogen-doped porous carbon nanospheres, nitrogen-doped carbon nanofibers, and nitrogen-doped carbon nanosheets; the mass content of nitrogen in the second nitrogen-doped porous carbon nanomaterial is 1-25%; and the specific surface area of the second nitrogen-doped porous carbon nanomaterial is 500-1500 m². 2 / g; D50 particle size of nitrogen-doped porous carbon nanospheres <1μm; the second nitrogen-doped porous carbon nanomaterial includes a fifth nitrogen-doped porous carbon nanomaterial and a sixth nitrogen-doped porous carbon nanomaterial; wherein, the mass ratio of the fifth nitrogen-doped porous carbon nanomaterial to the sixth nitrogen-doped porous carbon nanomaterial is 1:(0.1~0.5); the mass content of nitrogen in the fifth nitrogen-doped porous carbon nanomaterial is 5~15% lower than that in the sixth nitrogen-doped porous carbon nanomaterial; the specific surface area of the fifth nitrogen-doped porous carbon nanomaterial is 200~400m² smaller than that of the sixth nitrogen-doped porous carbon nanomaterial. 2 / g.
[0037] Preferably controlling the type of the second nitrogen-doped porous carbon nanomaterial spheres within the aforementioned range helps to improve the conductivity of the negative electrode, reduce polarization, and minimize side reactions. Simultaneously, it also facilitates the transfer of Mn atoms from the negative electrode surface via the lone pair electrons contained in the nitrogen atoms. 2+ By immobilizing the nitrogen through complexation, damage to the SEI film is reduced, thereby simultaneously achieving the dual functions of enhanced conductivity and improved cycle stability. Preferably, controlling the mass content of nitrogen in the second nitrogen-doped porous carbon nanomaterial within the aforementioned range helps to improve the conductivity of the negative electrode while simultaneously enhancing its resistance to Mn. 2+ The trapping ability of Mn is enhanced. Preferably, controlling the specific surface area of the second nitrogen-doped porous carbon nanomaterial within the above range helps to provide abundant active sites and enhance the trapping ability of Mn. 2+This enhances the capture capacity of the anode material and improves its liquid retention capacity, keeping the ion transport channels inside the battery unobstructed, thereby reducing electrolyte consumption and side reactions. Controlling the D50 particle size of nitrogen-doped carbon nanospheres within the aforementioned range helps them to be uniformly distributed in the anode active layer, thus simultaneously improving the conductivity and cycle stability of the anode material.
[0038] The nitrogen content in the second nitrogen-doped porous carbon nanomaterial can be 1%, 3%, 5%, 7%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 25%, etc. The specific surface area of the second nitrogen-doped porous carbon nanomaterial can be 500 m². 2 / g、700m 2 / g、900m 2 / g、1100m 2 / g、1200m 2 / g, 1500m 2 / g etc. The D50 particle size of nitrogen-doped porous carbon nanospheres can be 0.1μm, 0.3μm, 0.5μm, 0.7μm, 0.9μm, etc.
[0039] The preferred second nitrogen-doped porous carbon nanomaterial includes a fifth nitrogen-doped porous carbon nanomaterial and a sixth nitrogen-doped porous carbon nanomaterial with mass ratios within the above-mentioned range. By setting a gradient in nitrogen content and specific surface area between the two, their synergistic effect is enhanced, thereby further improving their conductivity and their affinity for Mn. 2+ The complexation ability of Mn is improved. Preferably, the nitrogen content in the fifth nitrogen-doped porous carbon nanomaterial is 3-8% by mass, and the nitrogen content in the sixth nitrogen-doped porous carbon nanomaterial is 12-20% by mass. Preferably, the nitrogen content in the fifth nitrogen-doped porous carbon nanomaterial is lower than that in the sixth nitrogen-doped porous carbon nanomaterial by the aforementioned range, which helps to form a gradient distribution of nitrogen, thereby improving the complexation ability of Mn. 2+ It improves the adsorption and complexation capacity and rate, while also enhancing the structural stability of nitrogen-doped porous carbon materials and reducing micropore collapse and pore blockage.
[0040] The preferred fifth nitrogen-doped porous carbon nanomaterial has a specific surface area of 500~800 m². 2 / g, the specific surface area of the sixth nitrogen-doped porous carbon nanomaterial is 1000~1200m². 2 / g, preferably, the specific surface area of the fifth nitrogen-doped porous carbon nanomaterial is smaller than that of the sixth nitrogen-doped porous carbon nanomaterial by the range mentioned above, which helps to form a gradient distribution of specific surface area, thereby achieving high conductivity and high Mn content. 2+ It achieves a compatibility between adsorption and complexation capacity and rate.
[0041] Fifth, nitrogen-doped porous carbon nanomaterials have relatively low nitrogen content and relatively small specific surface area, and mainly play a role in constructing the basic conductive network, thereby improving the overall electron transport efficiency of the negative electrode; sixth, nitrogen-doped porous carbon nanomaterials have relatively high nitrogen content and relatively large specific surface area, and mainly efficiently capture dissolved Mn. 2+ This reduces damage to the SEI film. The two work together to achieve "conductivity + retention" functional zoning: the fifth nitrogen-doped porous carbon nanomaterial with low nitrogen content and small specific surface area provides a stable framework, while the sixth nitrogen-doped porous carbon nanomaterial with high nitrogen content and large specific surface area focuses on interface protection.
[0042] An eighth nitrogen-doped porous carbon nanomaterial can be added as needed, with its nitrogen content and specific surface area falling between those of the fifth and sixth nitrogen-doped porous carbon nanomaterials, further optimizing the gradient effect of nitrogen content and specific surface area.
[0043] Preferably, the mass percentage of the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer is 0.1-0.5% higher than that of the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer, and the mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer is 1-3% higher than that in the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer. This facilitates the complexation and adsorption of Mn dissolved from the positive electrode by the first nitrogen-doped porous carbon nanomaterial in the positive electrode. 2+ Fe 2+ and Fe 3+ This reduces the amount of Mn dissolved at the positive electrode. 2+ Fe 2+ and Fe 3+ The amount of material migrating to the negative electrode improves the cell's cycle performance and high-temperature storage performance.
[0044] In one embodiment of this application, the negative electrode material is selected from any one or more of natural graphite, artificial graphite, and silicon carbon materials; and / or, the second conductive agent is conductive carbon black; and / or, the second binder is selected from any one or more of sodium carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber latex.
[0045] Preferably using a negative electrode material within the aforementioned range helps improve battery capacity and cycle performance. The second conductive agent is conductive carbon black, whose fine particles and uniform distribution help fill the gaps between negative electrode material particles, forming a continuous conductive path and thus improving electrode conductivity. Preferably using a second binder within the aforementioned range helps improve the adhesion of the negative electrode active layer, thereby improving the structural integrity of the electrode during long-term cycling and reducing active material peeling. Sodium carboxymethyl cellulose helps enhance the stability and adhesion of the slurry; polyacrylic acid has excellent adhesion and expansion buffering effects on silicon-based materials; and styrene-butadiene rubber latex helps improve electrode flexibility and interfacial bonding strength. Preferably, the second binder is a combination of sodium carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber latex, with a mass ratio of (0.5~1.5):(1.0~1.5):(1.5~2.5), which helps further improve the mechanical strength and structural stability of the negative electrode.
[0046] In another typical embodiment of this application, a method for preparing the above-mentioned lithium-ion battery is provided. The method includes: step S1, mixing raw materials including a positive electrode material, a first nitrogen-doped porous carbon nanomaterial, a first conductive agent, a first binder, and a first solvent to obtain a positive electrode slurry; coating the positive electrode slurry onto at least one side surface of a positive electrode current collector to form a positive electrode active layer to obtain a positive electrode sheet; step S2, mixing raw materials including a negative electrode material, a second nitrogen-doped porous carbon nanomaterial, a second conductive agent, a second binder, and a second solvent to obtain a negative electrode slurry; coating the negative electrode slurry onto at least one side surface of a negative electrode current collector to form a negative electrode active layer to obtain a negative electrode sheet; and step S3, assembling the positive electrode sheet, the separator, and the negative electrode sheet to obtain a lithium-ion battery.
[0047] The lithium-ion battery prepared by the method of this application exhibits excellent long-cycle performance, high energy density, and safety. Simultaneous addition of nitrogen-doped porous carbon nanomaterials to both the positive and negative electrode slurries achieves the following effects: 1) Nitrogen-doped porous carbon nanomaterials, through SP… 2 / SP 3 The synergistic effect of the hybrid carbon framework and nitrogen atoms can lower the Fermi level of the material to near the conduction band, while the lone pair electrons of nitrogen atoms increase the current density, thereby improving the conductivity of the electrode. 2) In nitrogen-doped porous carbon nanomaterials, the lone pair electrons of the nitrogen doped element can interact with Mn 2+ Complexation occurs, thereby dissolving the Mn from the LMFP cathode material. 2+ Fixed on its surface, preventing Mn 2+ The nitrogen-doped porous carbon nanomaterials in the negative electrode active layer can also migrate to the surface of the negative electrode. Simultaneously, the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer can also interact with the Mn²⁺ that dissolves from the positive electrode and migrates to the negative electrode region. + To generate a complexation effect and realize Mn2+ "In-situ capture" and "in-situ fixation" occur at the negative electrode interface. Therefore, through the synergistic complexation of the positive and negative electrodes, Mn can be effectively blocked. 2+ The catalytic destruction of the SEI film on the negative electrode avoids the continuous consumption of active lithium and electrolyte caused by repeated repair of the SEI film, thereby improving the cycle performance of the battery. 3) Nitrogen-doped porous carbon nanomaterials have a high specific surface area and high affinity for electrolyte, which can improve the electrolyte retention capacity of the electrode. This not only better maintains the smooth flow of ion transport channels inside the battery, reducing electrolyte consumption and side reactions, but also effectively reduces the direct contact between the electrolyte and electrode materials, reducing the occurrence of side reactions and thus extending the cycle life of the battery. At the same time, sufficient electrolyte can ensure the efficient diffusion of lithium ions between the positive and negative electrodes, thereby reducing polarization and improving the charge-discharge efficiency and cycle stability of the battery. In addition, the lithium-ion battery preparation method of this application is simple and can be mass-produced without modifying the production line.
[0048] In one embodiment of this application, in step S1 above, the first solvent is N-methylpyrrolidone; and / or, the solid content of the positive electrode slurry is 55-68%; and / or, the areal density of the single-sided positive electrode active layer is 87-91 g / m². 2 .
[0049] The preferred type of the first solvent is within the above-mentioned range, which helps the components to be fully dispersed in the first solvent and form a uniform positive electrode slurry. The preferred solid content of the positive electrode slurry and the density of the single-sided positive electrode active layer are within the above-mentioned range, which helps to maintain the coating fluidity of the positive electrode slurry and the compaction performance of the electrode sheet.
[0050] In one embodiment of this application, in step S2 above, the second solvent is water; and / or, the solid content of the negative electrode slurry is 48-58%; and / or, the areal density of the single-sided negative electrode active layer is 87-91 g / m². 2 .
[0051] Preferably, the type of the second solvent is within the above-mentioned range, which helps the components to be fully dispersed in the second solvent, forming a uniform negative electrode slurry and reducing agglomeration or sedimentation problems. Preferably, the solid content of the negative electrode slurry and the density of the single-sided negative electrode active layer are within the above-mentioned range, which helps to give the negative electrode active layer a certain porosity structure, thereby promoting electrolyte wetting and uniform lithium ion transport, and thus reducing the loss of active lithium and electrolyte caused by excessive repair of the SEI film.
[0052] The beneficial effects of this application will be further illustrated below with reference to the embodiments.
[0053] Example 1
[0054] Preparation of positive electrode:
[0055] 19 kg of the first solvent, N-methylpyrrolidone, was added to a double planetary stirred tank, followed by 1.0 kg of the first binder, polyvinylidene fluoride powder. The mixture was stirred at atmospheric pressure for 10 min, then under vacuum for 3 h to obtain the first binder solution. 16.8437 kg of the first binder solution was added to the stirred tank, followed by 2.144 kg of the first conductive agent, carbon nanotube slurry (solid content 4.8%), and 0.2 kg of the first nitrogen-doped porous carbon nanospheres (D50 = 0.25 μm, specific surface area 1041 m²). 2 The mixture consisted of 0.3 kg of acetylene black (a first conductive agent with a nitrogen content of 5.24%) and 5.5 kg of N-methylpyrrolidone (a first solvent). The mixture was stirred at atmospheric pressure for 10 min, then under vacuum for 1.5 h. Finally, 50 kg of lithium manganese iron phosphate (LiFe) was added as the positive electrode material. 0.5 Mn 0.5 PO4 and 3.5 kg of the first solvent, N-methylpyrrolidone, were stirred under normal pressure for 10 min and then under vacuum for 1.5 h to obtain a positive electrode slurry with a solid content of 65.55%. This positive electrode slurry was then coated onto one side of the carbon-coated aluminum foil of the positive electrode current collector using an extrusion coating process, resulting in an areal density of 220 g / m³. 2 After drying in an oven, the material is rolled up and then coated on the other side in the same way to obtain a double-sided coated positive electrode sheet; wherein the mass ratio of the positive electrode material, the first nitrogen-doped porous carbon nanospheres, the first conductive agent and the first binder is 97.2:0.4:0.8:1.6.
[0056] Preparation of negative electrode:
[0057] 18.747 kg of the second solvent, deionized water, was added to a double planetary stirred tank. 0.266 kg of the second binder, sodium carboxymethyl cellulose powder, was added. The mixture was stirred at atmospheric pressure for 10 min, followed by vacuum stirring for 3 h to obtain a sodium carboxymethyl cellulose adhesive solution. 40 kg of the negative electrode material, artificial graphite, was added to the double planetary stirred tank, followed by 0.106 kg of the second nitrogen-doped porous carbon nanospheres (D50 = 0.25 μm, specific surface area 1041 m²). 2The following ingredients were added: 0.1061 kg of acetylene black (a secondary conductive agent with a nitrogen content of 5.24%), stirred under normal pressure for 10 min, and then vacuum stirred for 0.5 h. Next, 7.552 kg of polyacrylic acid adhesive (a secondary binder), 8.397 kg of sodium carboxymethyl cellulose adhesive (a secondary binder), and 3.5 kg of deionized water (a secondary solvent) were added sequentially, and the mixture was stirred under vacuum for 1.0 h. Then, 7.447 kg of sodium carboxymethyl cellulose adhesive (a secondary binder) and 5.0 kg of deionized water (a secondary solvent) were added, and the mixture was stirred under vacuum for 4.0 h. Finally, 0.824 kg of styrene-butadiene rubber latex (a secondary binder) was added, and the mixture was stirred under vacuum for 1.0 h, yielding a negative electrode slurry with a solid content of 56.62%. This negative electrode slurry was then coated onto one side of the copper foil of the negative electrode current collector using an extrusion coating process, resulting in an areal density of 89 g / m². 2 After drying, the material is rolled up, flipped over, and coated again to obtain a double-sided coated negative electrode sheet. The mass ratio of the negative electrode material, the second nitrogen-doped porous carbon nanospheres, the second conductive agent, and the second binder is 96.88:0.26:0.26:2.6.
[0058] A polyolefin microporous membrane with a thickness of 12 μm, a porosity of 38%, and an average pore size of 0.05 μm was selected. The electrolyte consisted of 1.0 mol / Ld LiPF6 dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate (volume ratio 1:1:1), with 2 wt% fluoroethylene carbonate added as a film-forming aid.
[0059] The positive electrode, separator, and negative electrode are stacked in sequence to form a battery cell. The battery casing is then sealed to obtain the battery cell. Electrolyte is injected to obtain a lithium-ion battery.
[0060] Example 2
[0061] The difference from Example 1 lies in the preparation of the positive electrode: the first nitrogen-doped porous carbon spheres (D50 = 0.15 μm, specific surface area of 1500 m²) 2 / g, with a nitrogen content of 1%, and the first nitrogen-doped porous carbon sphere in the positive electrode active layer accounting for 1.0% of the mass, finally yielding the positive electrode sheet.
[0062] Preparation of the negative electrode: Second nitrogen-doped porous carbon spheres (D50=0.15μm, specific surface area of 1500m²) 2 / g, with a nitrogen content of 1%, and the second nitrogen-doped porous carbon sphere in the negative electrode active layer accounting for 1.0% of the mass, finally yielding the negative electrode sheet, and finally the lithium-ion battery.
[0063] Example 3
[0064] The difference from Example 1 lies in the preparation of the positive electrode: the first nitrogen-doped porous carbon sphere (D50 = 0.85 μm, specific surface area of 500 m²) 2 / g, with a nitrogen content of 25%, and the first nitrogen-doped porous carbon sphere in the positive electrode active layer accounting for 0.05% of the mass, finally yielding the positive electrode sheet.
[0065] Preparation of the negative electrode: Second nitrogen-doped porous carbon spheres (D50=0.85μm, specific surface area of 500m²) 2 / g, with a nitrogen content of 25%, and the second nitrogen-doped porous carbon sphere in the negative electrode active layer accounting for 0.05% of the mass, finally yielding the negative electrode sheet, and finally the lithium-ion battery.
[0066] Example 4
[0067] The difference from Example 1 lies in the preparation of the positive electrode: the first nitrogen-doped porous carbon nanomaterial is composed of a third nitrogen-doped porous carbon nanosphere and a fourth nitrogen-doped porous carbon nanosphere in a mass ratio of 1:0.1, wherein the specific surface area of the third nitrogen-doped porous carbon nanosphere is 500 m². 2 / g, with a nitrogen content of 3% by mass; the specific surface area of the fourth nitrogen-doped porous carbon nanosphere is 900m². 2 / g, with a nitrogen content of 18% by mass.
[0068] Preparation of the negative electrode: The second nitrogen-doped porous carbon nanomaterial is composed of fifth and sixth nitrogen-doped porous carbon nanospheres in a mass ratio of 1:0.1, wherein the specific surface area of the fifth nitrogen-doped porous carbon nanosphere is 500 m². 2 / g, with a nitrogen content of 3% by mass; the specific surface area of the sixth nitrogen-doped porous carbon nanospheres is 900m². 2 / g, with a nitrogen content of 18%, ultimately yields a lithium-ion battery.
[0069] Example 5
[0070] The difference from Example 1 lies in the preparation of the positive electrode: the first nitrogen-doped porous carbon nanomaterial is composed of a third nitrogen-doped porous carbon nanosphere and a fourth nitrogen-doped porous carbon nanosphere in a mass ratio of 1:0.8, wherein the specific surface area of the third nitrogen-doped porous carbon nanosphere is 800 m². 2 / g, with a nitrogen content of 8% by mass; the specific surface area of the fourth nitrogen-doped porous carbon nanosphere is 1000m². 2 / g, with a nitrogen content of 13% by mass.
[0071] Preparation of the negative electrode: The second nitrogen-doped porous carbon nanomaterial is composed of fifth and sixth nitrogen-doped porous carbon nanospheres in a mass ratio of 1:0.5, wherein the specific surface area of the fifth nitrogen-doped porous carbon nanosphere is 800 m². 2 / g, with a nitrogen content of 8% by mass; the specific surface area of the sixth nitrogen-doped porous carbon nanospheres is 1000m². 2 / g, with a nitrogen content of 13%, ultimately yields a lithium-ion battery.
[0072] Example 6
[0073] The difference from Example 1 lies in the preparation of the positive electrode: the first nitrogen-doped porous carbon nanomaterial is composed of a third nitrogen-doped porous carbon nanosphere and a fourth nitrogen-doped porous carbon nanosphere in a mass ratio of 2:1, wherein the specific surface area of the third nitrogen-doped porous carbon nanosphere is 800 m². 2 / g, with a nitrogen content of 1% by mass; the specific surface area of the fourth nitrogen-doped porous carbon nanosphere is 900m². 2 / g, with a nitrogen content of 20%.
[0074] Preparation of the negative electrode: The second nitrogen-doped porous carbon nanomaterial is composed of fifth and sixth nitrogen-doped porous carbon nanospheres in a mass ratio of 2:1, wherein the specific surface area of the fifth nitrogen-doped porous carbon nanosphere is 800 m². 2 / g, nitrogen content is 1% by mass; the specific surface area of the sixth nitrogen-doped porous carbon nanospheres is 900m². 2 / g, with a nitrogen content of 20%, ultimately yields a lithium-ion battery.
[0075] Example 7
[0076] The difference from Example 1 is that the mass percentage of the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 0.5%, and the mass percentage of the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer is 0.4%. The mass percentage of the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 0.1% higher than that of the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer. The mass content of nitrogen in the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 6%, and the mass content of nitrogen in the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer is 3%. The mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer is 3% higher than that in the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer, thus obtaining a lithium-ion battery.
[0077] Example 8
[0078] The difference from Example 1 is that the mass percentage of the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 0.7%, the mass percentage of the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer is 0.2%, the mass percentage of the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 0.5% higher than that of the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer, the mass content of nitrogen in the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 6%, the mass content of nitrogen in the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer is 5%, and the mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer is 1% higher than that in the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer, thus obtaining a lithium-ion battery.
[0079] Example 9
[0080] The difference from Example 1 is that the mass content of nitrogen in the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 0.05%, and the mass content of nitrogen in the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer is 1.0%. The mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer is 0.95% lower than that in the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer. The mass content of nitrogen in the first nitrogen-doped porous carbon nanospheres in the positive electrode active layer is 3%, and the mass content of nitrogen in the second nitrogen-doped porous carbon nanospheres in the negative electrode active layer is 6%. The mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer is 3% lower than that in the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer, thus obtaining a lithium-ion battery.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that the first nitrogen-doped porous carbon nanospheres in the positive electrode are replaced with the porous hollow g-C3N4 nanospheres in Example 1 of CN114628637A, and the second nitrogen-doped porous carbon nanospheres are not added to the negative electrode, thus obtaining a lithium-ion battery.
[0083] Comparative Example 2
[0084] The difference from Example 1 is that the lithium manganese iron phosphate material in the positive electrode is replaced with the positive electrode material in Example 1 of CN1120440862A, and the first nitrogen-doped porous carbon nanospheres are not added. The second nitrogen-doped porous carbon nanospheres are not added to the negative electrode, and a lithium-ion battery is finally obtained.
[0085] Comparative Example 3
[0086] The difference from Example 1 is that the positive electrode does not have the first nitrogen-doped porous carbon nanospheres added, and a lithium-ion battery is finally obtained.
[0087] Comparative Example 4
[0088] The difference from Example 1 is that no second nitrogen-doped porous carbon nanospheres are added to the negative electrode, resulting in a lithium-ion battery.
[0089] Test method:
[0090] Cell cycle performance test: According to GB / T 31484-2015 "Requirements and test methods for cycle life of power batteries for electric vehicles", 1000 cycles are performed at 25℃.
[0091] Test of manganese content in negative electrode: Take 10g of negative electrode sheet of the battery cell after 1000 cycles at 25℃, crush and grind it, put it into 100g of DMC solvent, stir and extract it thoroughly, separate it with a centrifuge, take the supernatant and test the manganese content. The specific test method is in accordance with HG / T 4067-2015 "Lithium Hexafluorophosphate Electrolyte".
[0092] The test results are shown in Table 1.
[0093] Table 1
[0094]
[0095] As shown above, the nitrogen content of the porous hollow g-C3N4 nanospheres in Comparative Example 1 is as high as about 55%. This excessively high nitrogen content causes the porous structure of the carbon material to collapse and blocks the pores, leading to reduced conductivity and Mn content. 2+ The adsorption capacity and adsorption rate decreased. In Comparative Example 2, no nitrogen-doped porous carbon nanospheres were added, and the sintering temperature during the preparation of the cathode material was below 800℃. The carbonization temperature of the porous carbon was low, resulting in more oxygen- and nitrogen-containing functional groups remaining, which led to an increase in battery side reactions and affected cycle performance.
[0096] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:
[0097] The lithium-ion battery of this application can synergistically solve the problems of low conductivity and Mn content in lithium manganese iron phosphate materials by simultaneously introducing nitrogen-doped porous carbon nanomaterials into both the positive and negative electrode active layers. 2+ The problem of deteriorated cycling performance due to dissolution. The specific principle is as follows: 1) Nitrogen-doped porous carbon nanomaterials are processed through SP... 2 / SP 3The synergistic effect of the hybrid carbon framework and nitrogen atoms can lower the Fermi level of the material to near the conduction band. Simultaneously, the lone pair electrons of nitrogen atoms increase the current density, increasing the conductivity of the conductive agent by approximately three times, thereby improving the conductivity of the electrode. This effectively alleviates the problem of severe polarization and increased side reactions during the charging and discharging process of the battery cell, which is caused by the low conductivity of LMFP materials, leading to performance degradation after long-term cycling. 2) In nitrogen-doped porous carbon nanomaterials, the lone pair electrons of the nitrogen doped element can interact with Mn... 2+ Complexation occurs, thereby dissolving the Mn from the LMFP cathode material. 2+ Fixed on its surface, preventing Mn 2+ The nitrogen-doped porous carbon nanomaterials in the negative electrode active layer can also migrate to the surface of the negative electrode. Simultaneously, the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer can also interact with the Mn dissolved from the positive electrode and migrated to the negative electrode region. 2+ To generate a complexation effect and realize Mn 2+ "In-situ capture" and "in-situ fixation" occur at the negative electrode interface. Therefore, through the synergistic complexation of the positive and negative electrodes, Mn can be effectively blocked. 2+ The damage to the SEI film on the negative electrode is prevented, avoiding repeated repairs that lead to continuous consumption of active lithium and electrolyte, thus improving the battery's cycle performance. 3) The high specific surface area of nitrogen-doped porous carbon nanomaterials gives them a high affinity for the electrolyte, enhancing the electrolyte retention capacity of the electrode. This not only better maintains the unobstructed ion transport channels inside the battery, reducing electrolyte consumption and side reactions, but also effectively reduces direct contact between the electrolyte and electrode materials, minimizing side reactions such as the catalytic decomposition of the electrolyte by manganese ions, thereby extending the battery's cycle life. Simultaneously, sufficient electrolyte ensures efficient diffusion of lithium ions between the positive and negative electrodes, reducing polarization and improving the battery's charge / discharge efficiency and cycle stability. In summary, the lithium-ion battery using the above-mentioned positive and negative electrodes exhibits excellent long-cycle performance, high energy density, and safety.
[0098] The above are merely embodiments of the present invention and are not intended to limit the invention. Those skilled in the art will recognize that the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A lithium-ion battery, comprising a positive electrode, a negative electrode, and a separator, wherein the positive electrode includes a positive current collector and a positive active layer disposed on at least one surface of the positive current collector, and the negative electrode includes a negative current collector and a negative active layer disposed on at least one surface of the negative current collector, characterized in that, The positive electrode active layer comprises a positive electrode material, a first nitrogen-doped porous carbon nanomaterial, a first conductive agent, and a first binder. The positive electrode material comprises lithium manganese iron phosphate. The mass percentage of the first nitrogen-doped porous carbon nanomaterial in the positive electrode active layer is 0.05% to 1.0%. The negative electrode active layer comprises a negative electrode material, a second nitrogen-doped porous carbon nanomaterial, a second conductive agent, and a second binder; the mass percentage of the second nitrogen-doped porous carbon nanomaterial in the negative electrode active layer is 0.05~1.0%.
2. The lithium-ion battery according to claim 1, characterized in that, The mass ratio of the positive electrode material, the first nitrogen-doped porous carbon nanomaterial, the first conductive agent, and the first binder in the positive electrode active layer is (94~98):(0.05~1):(0.2~2.5):(1~3.5).
3. The lithium-ion battery according to claim 1 or 2, characterized in that, The first nitrogen-doped porous carbon nanomaterial is selected from any one or more of nitrogen-doped porous carbon nanospheres, nitrogen-doped carbon nanofibers, and nitrogen-doped carbon nanosheets; the mass content of nitrogen in the first nitrogen-doped porous carbon nanomaterial is 1-25%; the specific surface area of the first nitrogen-doped porous carbon nanomaterial is 500-1500 m². 2 / g; The D50 particle size of the nitrogen-doped porous carbon nanospheres is <1μm; The first nitrogen-doped porous carbon nanomaterial includes a third nitrogen-doped porous carbon nanomaterial and a fourth nitrogen-doped porous carbon nanomaterial; wherein the mass ratio of the third nitrogen-doped porous carbon nanomaterial to the fourth nitrogen-doped porous carbon nanomaterial is 1:(0.1~0.8); the mass content of nitrogen in the third nitrogen-doped porous carbon nanomaterial is 5~15% lower than the mass content of nitrogen in the fourth nitrogen-doped porous carbon nanomaterial; The specific surface area of the third nitrogen-doped porous carbon nanomaterial is 200-400 μm smaller than that of the fourth nitrogen-doped porous carbon nanomaterial. 2 / g.
4. The lithium-ion battery according to any one of claims 1 to 3, characterized in that, The cathode material also includes any one or more of lithium iron phosphate, lithium-rich manganese-based cathode materials, and ternary cathode materials; And / or, the first conductive agent is conductive carbon black and / or carbon nanotubes; when the first conductive agent is a combination of the conductive carbon black and the carbon nanotubes, the mass ratio of the conductive carbon black to the carbon nanotubes is 0.3~1.5:0.05~1.0; And / or, the first adhesive is polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer.
5. The lithium-ion battery according to any one of claims 1 to 4, characterized in that, The mass ratio of the negative electrode material, the second nitrogen-doped porous carbon nanomaterial, the second conductive agent, and the second binder in the negative electrode active layer is (94~98):(0.05~1):(0.2~2.5):(1~3.5).
6. The lithium-ion battery according to any one of claims 1 to 5, characterized in that, The second nitrogen-doped porous carbon nanomaterial is selected from any one or more of nitrogen-doped porous carbon nanospheres, nitrogen-doped carbon nanofibers, and nitrogen-doped carbon nanosheets; the mass content of nitrogen in the second nitrogen-doped porous carbon nanomaterial is 1-25%; the specific surface area of the second nitrogen-doped porous carbon nanomaterial is 500-1500 m². 2 / g; The D50 particle size of the nitrogen-doped porous carbon nanospheres is <1μm; The second nitrogen-doped porous carbon nanomaterial includes a fifth nitrogen-doped porous carbon nanomaterial and a sixth nitrogen-doped porous carbon nanomaterial; wherein the mass ratio of the fifth nitrogen-doped porous carbon nanomaterial to the sixth nitrogen-doped porous carbon nanomaterial is 1:(0.1~0.5); the mass content of nitrogen in the fifth nitrogen-doped porous carbon nanomaterial is 5~15% lower than the mass content of nitrogen in the sixth nitrogen-doped porous carbon nanomaterial. The specific surface area of the fifth nitrogen-doped porous carbon nanomaterial is 200-400 μm smaller than that of the sixth nitrogen-doped porous carbon nanomaterial. 2 / g.
7. The lithium-ion battery according to any one of claims 1 to 6, characterized in that, The negative electrode material is selected from any one or more of natural graphite, artificial graphite, and silicon carbide materials; And / or, the second conductive agent is conductive carbon black; And / or, the second adhesive is selected from any one or more of sodium carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber latex.
8. A method for preparing a lithium-ion battery according to any one of claims 1 to 7, characterized in that, The preparation method includes: Step S1: Mix raw materials including positive electrode material, first nitrogen-doped porous carbon nanomaterial, first conductive agent, first binder and first solvent to obtain positive electrode slurry; coat the positive electrode slurry on at least one side surface of the positive electrode current collector to form a positive electrode active layer, and obtain a positive electrode sheet; Step S2: Mix the raw materials of the negative electrode material, the second nitrogen-doped porous carbon nanomaterial, the second conductive agent, the second binder, and the second solvent to obtain a negative electrode slurry; coat the negative electrode slurry on at least one side of the negative electrode current collector to form a negative electrode active layer, thereby obtaining a negative electrode sheet; Step S3: Assemble the positive electrode, separator and negative electrode to obtain the lithium-ion battery.
9. The preparation method according to claim 8, characterized in that, In step S1, the first solvent is N-methylpyrrolidone; and / or, the solid content of the positive electrode slurry is 55-68%; and / or, the areal density of the positive electrode active layer on one side is 87-91 g / m². 2 .
10. The preparation method according to claim 8 or 9, characterized in that, In step S2, the second solvent is water; and / or, the solid content of the negative electrode slurry is 48-58%; and / or, the areal density of the negative electrode active layer on one side is 87-91 g / m². 2 .
Citation Information
Patent Citations
Preparation method of high-conductivity lithium iron phosphate positive plate
CN114628637A